Hematological parameters in pediatric patients with primary headache - Aksoy, Erhan (Annals of Medical Research, 2021)
Aim: The present study aimed to evaluate the pain parameters in children with primary headache according to the International Classification of Headache Disorders, 3rd edition, diagnostic criteria and to investigate the role of hematological parameters in diagnosis in case the distinguish is difficult especially in children with migraine and tension headache.Materials and Methods: Medical data belonging age, gender, headache characteristics, hematological parameters of the outpatients with headache consulted in Beştepe Child Neurology Outpatient Clinic of Dr. Sami Ulus Children's Hospital between July 2017 and August 2019 were examined retrospectively. SPSS statistical software was used to perform statistical data analysis. Results: A total of 243 patients (151 female, 92 male) were included in the study. The mean age was 13.68 ± 2.25 years. One hundred and one (58 female, 43 male) patients were diagnosed with migraine and 142 (93 female, 49 male) with tension type headache. Migraine presented the characteristics of unilateral (61.2%), pulsatile (88.5%) headache of moderate to severe intensity that worsens with physical activity, occurs usually in mornings (%46,5) and is accompanied by nausea or by photophobia and phonophobia (%34,3). Tension-type headache presented the characteristics of circumferential (53,2%), pressing (87.7%) headache of mild severe intensity that is triggered by school stress and accompanied phonophobia (65.2%), and occurs usually in evenings (55.3%). White blood cells, neutrophil, monocyte, monocyte-lymphocyte ratio and neutrophil-lymphocyte ratio were significantly higher in patients with migraine and lymphocyte and platelet counts were significantly higher in patients with tension type headache.Conclusion: In terms of shining a light on the future, consideration of the contribution of hematological parameters to differential diagnosis as a diagnostic support, due to the difficulties associated in particular with the presence of overlapping symptoms in the differential diagnosis of migraine and tension headache in childhood could make a significant difference.
Keywords: Childhood primary headaches; migraine; tension-type headache; hematological parameters; monocyte lymphocyte ratio; neutrophil lymphocyte ratio